Ana Ozores y Malena: pervivencia de unos caracteres - Barrera García, Consuelo (Huarte de San Juan. Filología y Didáctica de la Lengua, 1999)
Twentieth-century novel is the result of the evolution which narrative has experimented from the 19th century up to nowadays. However, current narrations still recreate the same nineteenth-century themes of seduction and adultery. This is the case of “Malena es un nombre de tango” with regard to “La Regenta”. Both novels present heroines with similar features, together with main characters showing the same actions, ideas and thoughts, at the same rime repeated by means of the same objects, which imply a similar semiotic meaning. All this helps outline the unity of this work.